RANCANG BANGUN ALAT UKUR ANTROPOMETRI DIGITAL DAN PORTABEL [DESIGN AND CONSTRUCTION OF DIGITAL AND PORTABLE ANTHROPOMETRIC MEASUREMENT TOOLS] - Nicholaus Matthew; Agustina Christiani; Christopher Nata (Universitas Pelita Harapan, 2023)
In the Work System Design Laboratory at UPH, there are anthropometric measuring tools for standing position and sitting position. Based on the tools evaluation, it was found that they were less efficient because of the need for repeated tool adjustments. Furthermore, two observers were needed to collect anthropometric data and they had to read the scale manually. Therefore, a new digital and portable anthropometric measuring tool was developed to overcome the problem. The Gea HT721 measuring instrument was chosen as an alternative to a new anthropometric measuring tool that uses ultrasonic ranging technology to measure distances. A supporting tool (similar to a caliper) was also developed to support the anthropometric measurement process. An evaluation of the new anthropometric measuring tool was carried out by calculating the average percent error and a comparison of the total time for data collection. The results of the average percent measurement error was 0.58%. According to the paired t-test, there was no significant difference in the average of measured body dimensions using the new and the previous tools. The new anthropometric tools can reduce data collection time by 32% for standing positions and 11% for sitting positions.Bahasa Indonesia Abstract:Pada Laboratorium Analisis Perancangan Kerja (APK) di UPH terdapat alat ukur antropometri posisi berdiri dan posisi duduk. Berdasarkan evaluasi alat antropometri tersebut, ditemukan bahwa alat kurang efisien karena membutuhkan penyetelan alat yang berulang yang juga membutuhkan lebih dari satu pengamat saat pengambilan data. Selain itu, pengamat sering mengalami kesulitan pembacaan hasil pengukuran manual pada meteran. Oleh karena itu, dibuat alat antropometri jenis baru yang bersifat digital dan portabel. Alat ukur Gea HT721 dipilih sebagai alternatif alat antropometri baru yang menggunakan teknologi ultrasonic ranging untuk mengukur jarak. Setelah itu, dirancang dan dibuat suatu alat pendukung yang menyerupai jangka sorong untuk mendukung proses pengukuran data antropometri. Evaluasi alat antropometri baru dilakukan dengan menghitung rata - rata persen error, serta perbandingan total waktu pengambilan data. Hasil rata - rata persen error pengukuran adalah 0,58%. Hasil uji paired t test menunjukkan bahwa tidak terdapat perbedaan signifikan antara rata-rata hasil pengukuran dimensi tubuh menggunakan alat ukur antropometri jenis baru dengan hasil pengukuran menggunakan alat yang lama. Berdasarkan perbandingan total waktu pengambilan data terdapat penurunan waktu sebesar 32% untuk data antropometri posisi berdiri dan 11% untuk data antropometri posisi duduk.